2006
DOI: 10.1111/j.1369-1600.2006.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW: Modulation of high alcohol drinking in the inbred Fawn–Hooded (FH/Wjd) rat strain: implications for treatment

Abstract: The Fawn-Hooded rat (FH/Wjd) is an inbred alcohol-preferring rat strain, unlike most of the other strains that were selectively bred for high alcohol intake and preference. It was chosen for study some 16 years ago because of a reported mutation that disrupted platelet serotonin function. Although the FH/Wjd rat has high alcohol intake (>5 g/kg/day) and preference (>65%), interbreeding with an alcohol-non-preferring inbred strain suggested that these measures are unrelated to the serotonin abnormality. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 151 publications
0
8
0
Order By: Relevance
“…Preclinical and clinical research indicates the following endophenotypes are directly related to the development of ethanol dependence (a) lower initial sensitivity to ethanol's aversive effects (c.f., Bell et al, 2006b, 2012; Colombo et al, 2006; Draski and Deitrich, 1996; Le et al, 2001b; Schuckit and Gold, 1988), (b) greater levels and/or quicker development of ethanol-induced tolerance (c.f., Costin and Miles, 2014; Lê and Mayer, 1996), (c) anxiety-like and/or depressive behavior including during ethanol withdrawal (c.f., Ciccocioppo et al, 2006; Heilig et al, 2010; Kirby et al, 2011; Overstreet et al, 2006; Pautassi et al, 2010; Sjoerds et al, 2014; Thorsell, 2010), (d) stress reactivity (c.f., Barr and Goldman, 2006), and (e) sweet liking/preference (c.f., de Wit and Richards, 2004; Kampov-Polevoy et al, 2014; Lange et al, 2010; Pepino and Mennella, 2007; Perry and Carroll et al, 2008). …”
Section: Background From a Clinical Perspectivementioning
confidence: 99%
“…Preclinical and clinical research indicates the following endophenotypes are directly related to the development of ethanol dependence (a) lower initial sensitivity to ethanol's aversive effects (c.f., Bell et al, 2006b, 2012; Colombo et al, 2006; Draski and Deitrich, 1996; Le et al, 2001b; Schuckit and Gold, 1988), (b) greater levels and/or quicker development of ethanol-induced tolerance (c.f., Costin and Miles, 2014; Lê and Mayer, 1996), (c) anxiety-like and/or depressive behavior including during ethanol withdrawal (c.f., Ciccocioppo et al, 2006; Heilig et al, 2010; Kirby et al, 2011; Overstreet et al, 2006; Pautassi et al, 2010; Sjoerds et al, 2014; Thorsell, 2010), (d) stress reactivity (c.f., Barr and Goldman, 2006), and (e) sweet liking/preference (c.f., de Wit and Richards, 2004; Kampov-Polevoy et al, 2014; Lange et al, 2010; Pepino and Mennella, 2007; Perry and Carroll et al, 2008). …”
Section: Background From a Clinical Perspectivementioning
confidence: 99%
“…In particular, a number of neurochemical differences were found in genetically selected alcohol‐preferring rat lines as compared with non‐preferring lines. The most commonly used lines are the Finnish alcohol‐preferring (AA), the Sardinian‐preferring (SP), the Indiana University alcohol‐preferring (P) and the HAD rat lines ( Bell et al ., 2006 ; Ciccocioppo et al ., 2006 ; Overstreet et al ., 2006 ; Sommer et al ., 2006 ). As an example, low levels of DA and 5‐HT in several limbic structures were seen in alcohol‐preferring P and HAD rat lines in comparison to their alcohol non‐preferring counterparts.…”
Section: Maintenance Of Alcohol Consumptionmentioning
confidence: 99%
“…Specifically, we explored whether the combination of DP with NTX could suppress the delayed ADE, i.e., the rebound in alcohol consumption detected in animal laboratory models after continuous blockade of the opioid receptor with antagonists such as NTX (Heyser et al, 2003) or naloxone (Hölter and Spanagel, 1999). In this sense, in several strains of rats using free choice paradigms it has been demonstrated that NTX decreases ethanol consumption (Overstreet et al, 2006), however, tolerance to this effect was demonstrated after repeated drug administration, leading to an increase in alcohol consumption (Cowen et al, 1999; Juárez and Eliana, 2007). This fact is probably due to the MORs up-regulation associated with its continuous blockade (Hyytiä et al, 1999; Overstreet et al, 1999; Orrico et al, 2014).…”
Section: Introductionmentioning
confidence: 99%